Sharia Crowdfunding Securities Development Model with Analytical Network Process (ANP) Approach - Muhammad Ikhsan Harahap; Nurhayati; Marliyah; Yusrizal; Ilhamy Nasution, Muhammad Lathief; Ramil Abbasov (Universitas Muhammadiyah Yogyakarta, 2025)
This research aims to develop a model for Islamic securities crowdfunding in Indonesia. Respondents consisted of 9 experts, including regulators, SCF operators, academics, MSMEs, and representatives of the Islamic fintech association, selected through purposive sampling. This research uses the Analytical Network Process (ANP) approach model. The results indicated that the problems encountered in the development of Islamic crowdfunding securities comprise five key aspects: literacy, public trust, management, regulatory, and technological. The level of agreement (rater agreement) is W=0.3753086, indicating 37.5% sufficient agreement in determining the problem priority issues among informants. The most prioritized Islamic crowdfunding securities development solution is the literacy solution, followed by the public trust solution, the technology solution, the management solution, and finally the regulatory solution. The informants’ agreement level is W = 0.2938272. This means that the level of agreement among informants on the priority order of Islamic SCF development solutions is 29.3%, indicating a sufficient level of agreement. Alternative strategies for developing the most prioritized Islamic crowdfunding securities include increasing literacy, building ecosystems, securing government support, improving technology, and implementing business sustainability strategies. The level of agreement (rater agreement) is W = 0.3101343, indicating that the priority order of Islamic SCF development strategies is 31% agreement, which is a sufficient level.